Образ Нарциса і нарцисизм у творчості Овідія та Оскара Вайлда - Гладка, Н. (Літературознавчі обрії. Праці молодих учених, 2010)
The place and symbolism of Narcissus’ image and in Ovid’s and Wilde’s works are investigated in the article. The interpretations are performed on the basis of the novel «The Picture of Dorian Gray» by Oscar Wilde and «Metamorphoses» by Ovid. Particular attention is paid to similar motives.